Analysis of the Impact of Mobile Applications for the Monitoring of Hospitalized Patients: A Review of the Scientific Literature from 2015-2020 - Edson De la Cruz-Peña; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2020)
The document uses a review of the scientific literature from 2015-2020 to know the criteria, tools, architecture and definitions that this technology provides in this health sector, summarizes an architectural framework and methodology, and provides conclusions. The most popular journals included IEEE Xplore, Science Direct, SCIELO, ACM Digital Library. 75 related articles were produced from the search, then reviewed. The study concluded that there were four most used tools for the development of mobile tracking applications, three types of most used architectures. The analysis of mobile applications in the health sector is being promoted in a promising domain to provide information on the internment process.
Keywords: Mobile application; Patients monitoring; Systematic review of the literature.